The Effect of Charismatic Leadership and Motivation on Employee Performance Mediated by Work Discipline at PT. Payung Indonesia Kuat - Engkus Kusnadi; Anna Wulandari; Sarwo Edy (UNIVED Press, 2024)
This study aims to determine The Effect of Charismatic Leadership and Motivation on Employee Performance Mediated by Work Discipline at PT. Payung Indonesia Kuat, Bekasi City. Respondents of this study were 60 respondents and this study used a quantitative approach with the SmartPLS 3.0 data processing application. The results of this study found that 1. Charismatic leadership has a positive and significant effect on work discipline, 2. Motivation has a positive and significant effect on work discipline, 3. Work discipline has a positive and significant effect on employee performance, 4. Charismatic leadership has a positive and significant effect on employee performance, 5. Motivation has a positive and significant effect on employee performance, 6. Charismatic leadership has a positive and significant effect on employee performance through work discipline, 7. Motivation has a positive and significant effect on employee performance through work discipline.